Correlation Between the Distribution of Oxide Functional Groups and Electrocatalytic Activity of Glassy Carbon Surface - Vettorazzi, Nelio Roberto (2008)
Oxidative electrochemical pretreatment on glassy carbon GC electrodes in aqueous media produces changes in the relative densities of oxidized species present on the material surface. These changes vary with both applied potential and time procedure. The GC surface oxidation treatment not only increases the oxygen-containing group coverage but also causes lattice damage, producing a highly porous dielectric film. In this work we report the gradual relationship between the kinetics of the heterogeneous charge transfer after different pretreatment procedures and the surface distribution of oxidized species in GC measured through electron spectroscopy for chemical analysis. The lack of faradaic current observed when the electrode surface is oxidized under the constant-potential regime is proposed to be due to changes in the lattice structure, observed by scanning electron microscopy. This fact is important in systems where carbon materials are used as electrodes under the continuous-oxidation regime, such as high-performance liquid chromatography electrochemical detectors, batteries, capacitors, and for the generation of polymers by potentiostatic oxidation. densities of oxidized species present on the material surface. These changes vary with both applied potential and time procedure. The GC surface oxidation treatment not only increases the oxygen-containing group coverage but also causes lattice damage, producing a highly porous dielectric film. In this work we report the gradual relationship between the kinetics of the heterogeneous charge transfer after different pretreatment procedures and the surface distribution of oxidized species in GC measured through electron spectroscopy for chemical analysis. The lack of faradaic current observed when the electrode surface is oxidized under the constant-potential regime is proposed to be due to changes in the lattice structure, observed by scanning electron microscopy. This fact is important in systems where carbon materials are used as electrodes under the continuous-oxidation regime, such as high-performance liquid chromatography electrochemical detectors, batteries, capacitors, and for the generation of polymers by potentiostatic oxidation. GC electrodes in aqueous media produces changes in the relative densities of oxidized species present on the material surface. These changes vary with both applied potential and time procedure. The GC surface oxidation treatment not only increases the oxygen-containing group coverage but also causes lattice damage, producing a highly porous dielectric film. In this work we report the gradual relationship between the kinetics of the heterogeneous charge transfer after different pretreatment procedures and the surface distribution of oxidized species in GC measured through electron spectroscopy for chemical analysis. The lack of faradaic current observed when the electrode surface is oxidized under the constant-potential regime is proposed to be due to changes in the lattice structure, observed by scanning electron microscopy. This fact is important in systems where carbon materials are used as electrodes under the continuous-oxidation regime, such as high-performance liquid chromatography electrochemical detectors, batteries, capacitors, and for the generation of polymers by potentiostatic oxidation.